Natural vegetation based landscape indicators for Hungary I.: critical review and the basic ‘MÉTA’ indicators - Molnár, Zsolt; Horváth, Ferenc (TÁJÖKOLÓGIAI LAPOK, 2008)
In the present article we give a critical review about those biodiversity indicators that are in connection with the landscape and the vegetation. Besides, we describe the indicators deriving from the only GIS database, which contains ecologically relevant data for the whole territory of Hungary. Quantity area, pattern, quality and combined indicators are used globally and at the scale of Europe. Most of these are ecologically irrelevant, principally due to the lack of relevant data. Few indicators are actually employed, but developments are still in progress. On the grounds of the MÉTA database Landscape Ecological Vegetation Database for Hungary, constructed between 2002 and 2008, we propose the use of the following landscape and vegetation indicators for Hungary: habitat area, habitat texture of the landscape, area of old-fields, regional coverage of invasive species, habitat diversity, Natural Capital Index, area of high value natural areas, proportion of naturalness classes, structural habitat connectivity. Some of these indicators would also be applicable in the Hungarian Biodiversity Monitoring System. In the future, there will be serious need for the elaboration and testing of further indicators, as well as for their detailed definition and their introduction in practice.